Utility of galectin-3 in predicting post-infarct remodeling after acute myocardial infarction based on extracellular volume fraction mapping. (15th November 2016) - Perea, Rosario J.; Morales-Ruiz, Manuel; Ortiz-Perez, Jose T.; Bosch, Xavier; Andreu, David; Borras, Roger; Acosta, Juan; Penela, Diego; Prat-González, Susanna; de Caralt, Teresa M.; Martínez, Mikel; Morales-Romero, Blai; et al.
Abstract: Aims: ST-segment elevation myocardial infarction (STEMI) triggers remote extracellular matrix expansion. Myocardial extracellular volume fraction (ECV), determined by cardiovascular magnetic resonance, permits quantification of interstitial space expansion. Our aim was to determine the relationship between early serum fibrosis biomarkers and 180-day post-infarct remote myocardium remodeling using ECV. Methods and results: In 26 patients with STEMI, functional imaging, T1-mapping, and late-gadolinium-enhancement were performed on a 3-T CMR scanner at baseline (days 3 to 5) and 180 days. Biomarkers were measured at days 1, 3, and 7 after STEMI. The mean initial and follow-up left ventricular ejection fraction (LVEF) were 48.3 ± 18.1% and 52.6 ± 12.3%, respectively. Initial infarct size was 11.6 ± 16.8% of LV mass. ECV in the remote myocardium at 180 days correlated with indexed end-systolic volume (r = 0.4, p = 0.045). A significant correlation was observed between galectin-3 at day 7 and ECV at 6 months (r = 0.428, p = 0.037). A trend towards a direct correlation was found for BNP (r = 0.380, p = 0.059). Multivariate analysis revealed that BNP and galectin-3 were independent predictors of long-term changes in ECV and explained nearly 30% of the variance in this parameter (r 2  = 0.34; p = 0.01). A galectin-3 cutoff value of 10.15 ng/mL was the most powerful predictor of high ECV values (≥ 28.5%) at follow-up. Galectin-3 at day 7 was an independent predictor of high ECV values at follow-up (OR = 22.51; CI 95%: 2.1–240.72; p = 0.01) with 0.76 AUC (CI: 0.574–0.964; p = 0.03). Conclusions: Galectin-3 measured acutely after STEMI is an independent predictor of increased ECV at 6-month follow-up that might be useful for long-term risk stratification.